1980
DOI: 10.1093/infdis/142.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Experimental Enterocecitis Due to Clostridium dlfficile

Abstract: Hamsters can survive a course of clindamycin if they are held in a protected environment. Inoculation of Clostridium difficile regularly results in fatal enterocecitis in such animals but is without effect in untreated animals. These findings suggest that in the development of enterocecitis, clindamycin treatment and infection with C. difficile are separate events, and they imply that hamsters usually acquire C. difficile from environmental sources. Environments appear to differ in the risk of exposure to C. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 21 publications
3
27
1
Order By: Relevance
“…Diet contributed to the development of antibiotic-associated diarrhea in hamsters in one study, and intestinal pH may be a factor.24 C. digicile toxin production can be altered in vivo by feeding different diets.23 Diets high in fat can affect both cell-mediated and humoral i m m~n i t y , l~.~~.~~ and diets high in cholesterol can alter membrane fl~idity.~ The high-fat, highcholesterol diet may cause alterations in the microbial populations in the intestine similar to the alterations caused by certain antibiotics that increase susceptibility to C. dijicile disease. 20,22 In the present studies, no significant differences in the cecal microbial flora were observed between the atherogenic and control diet groups (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
“…Diet contributed to the development of antibiotic-associated diarrhea in hamsters in one study, and intestinal pH may be a factor.24 C. digicile toxin production can be altered in vivo by feeding different diets.23 Diets high in fat can affect both cell-mediated and humoral i m m~n i t y , l~.~~.~~ and diets high in cholesterol can alter membrane fl~idity.~ The high-fat, highcholesterol diet may cause alterations in the microbial populations in the intestine similar to the alterations caused by certain antibiotics that increase susceptibility to C. dijicile disease. 20,22 In the present studies, no significant differences in the cecal microbial flora were observed between the atherogenic and control diet groups (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
“…All the animals were housed individually in sterile isolator cages with sterilised food and bedding (Larson et al,, 1980); 5 days later they were killed and their caecal contents were harvested and diluted 20-fold w/v in sterile distilled water. The caecal material obtained from the untreated hamsters was pooled and a portion was centrifuged at 12 000 rpm for 30 min and filtered through a 0.20-pm membrane filter.…”
Section: Growth Of C Dificile In Faecal Emulsions Derivedfrom Patienmentioning
confidence: 99%
“…There is much evidence to imply that a stable normal gut flora acts as a natural barrier to infection with C. dzficile (Bowden et al, 1981;Wilson et al, 1981;Borriello and Barclay, 1984;Schwan et al, 1984), and that infection with C. dzficile generally requires recent or current antimicrobial therapy to disrupt the gut flora and create an intestinal environment conducive to growth of C. dzficile and production of its toxins. In the Syrian hamster model of PMC, disease is induced by the administration of antibiotics which disrupt the normal gut flora and subsequent exposure to pathogenic strains of C. dzficile; neither antibiotic treatment nor exposure to C. dzficile alone is sufficient to produce disease if animals are housed in protected (i.e., C. dzficile-free) environments (Larson et al, 1980). Many attempts have been made to identify the individual components of the faecal flora that are antagonistic to C. dzficile in vitro (Rolfe et al,198 1 ; Borriello, 1982 Received 19 Jul.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental contamination has been suggested as a significant factor in the transmission of C. dificile (Fekety et al, 1980;Larson et al, 1980). Survival of C. dificile in an aerobic environment is possible because this obligate anaerobe can form aerotolerant spores; there are reports that C. dzficile can survive for > 5 months in aerobic conditions (Kim et al, 1981).…”
Section: Introductionmentioning
confidence: 99%